2022
DOI: 10.1101/2022.06.28.497990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GLT8D1 mutations cause amyotrophic lateral sclerosis via disruption of neurotrophin signalling within membrane lipid rafts

Abstract: Mutations within GLT8D1 contribute to familial amyotrophic lateral sclerosis. Pathogenic mutations impair GLT8D1 glycosyltransferase enzymatic function via a dominant negative mechanism, yet the downstream mechanism leading to neurotoxicity is unclear. Here we show that a p.R92C mutation causes fragmentation of the Golgi network and reduces ganglioside expression within membrane lipid rafts (MLRs), leading to impaired neurotrophin signalling. Expression of p.R92C-GLT8D1 in HEK293 cells and mouse primary neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Potential candidates could be glycolipids, which are known to be relevant in signaling events associated with neurodegeneration 42 and cancer 43 . In this context, recent evidence indicated that GLT8D1 was relevant in ganglioside biosynthesis 16 . Glycoproteins could also constitute potential substrates; for example, the T-antigen and related structures are present in mucins with important roles in cancer 44 and sialylated T-antigen is abundantly expressed in brain tissue glycoproteins [45][46][47] , but the enzymes involved in their biosynthesis have been well-studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential candidates could be glycolipids, which are known to be relevant in signaling events associated with neurodegeneration 42 and cancer 43 . In this context, recent evidence indicated that GLT8D1 was relevant in ganglioside biosynthesis 16 . Glycoproteins could also constitute potential substrates; for example, the T-antigen and related structures are present in mucins with important roles in cancer 44 and sialylated T-antigen is abundantly expressed in brain tissue glycoproteins [45][46][47] , but the enzymes involved in their biosynthesis have been well-studied.…”
Section: Discussionmentioning
confidence: 99%
“…GLT8D1 is also associated with cancer: a mutation in GLT8D1 was found in soft tissue tumors 12 ; it was proposed as prognostic marker for melanoma 13 and gastric cancer where it correlated with tumor immunity markers 14 ; it promoted human glioblastoma cell migration 15 . More recently, evidence supported a role of GLT8D1 in neurotrophin signaling within membrane lipid rafts 16 .…”
mentioning
confidence: 96%